Recensión de ALENZA GARCÍA, J. F., El Derecho en la obra de Lorenzo Silva, Thomson Reuters- Aranzadi, 395 pp. - LÓPEZ GARCÍA, MABEL (Revista Jurídica de Investigación e Innovación Educativa (REJIE Nueva Época), 2016)